Development and evaluation of a specifically designed website for haematopoietic stem cell transplant patients in Leeds. (27th July 2015) - Horne, B.; Newsham, A.; Velikova, G.; Liebersbach, S.; Gilleece, M.; Wright, P.
Abstract : The purpose of this project was to develop and evaluate a specifically designed website (ALLograft INformation EXchange – ALLINEX) for adult allogeneic haematopoietic stem cell transplant (allo‐HSCT) patients in Leeds. Specifications included information on the transplant journey and supportive care services, discussion forum and patient‐clinical team electronic messaging service. The method followed a participatory action research approach in a five‐phase project involving stakeholders. Phase 1 involved information gathering; Phase 2 development of content; Phase 3 building of website and usability testing; Phase 4 preliminary evaluation; and Phase 5 clinical implementation. Results concluded that Phase 1 patients were unaware of all services and reported unmet needs; gaps in support services were identified from a service evaluation; Phase 2 content was collected from experts, collated and synthesised; Phase 3 patient and staff feedback was positive and constructive resulting in more than 50 changes; Phase 4 ALLINEX evaluation demonstrated acceptable usability with good layout, content and aesthetics reported; Phase 5, over 15 weeks, ALLINEX had 6630 page hits, 9 new forum topics posted and received 3 clinical messages. The clinical team embraced responsibility for reviewing and monitoring ALLINEX. Financial and indemnity cover was secured for 3 years. ALLINEX, adopted locally, is sustainable and has functionality to roll‐out to other UK allo‐HSCT centres.